Let [MATH]f:\mathbb{R} \to \mathbb{R}[/MATH] be a function and let [MATH]f[/MATH] differentiable in [MATH]x=0[/MATH]. Show that
[MATH]\lim_{x \to 0} \frac{f(x^2)-f(0)}{x}=0[/MATH]My try: [MATH]f[/MATH] is differentiable in [MATH]x=0[/MATH], so from the Taylor formula with center in [MATH]x=0[/MATH] it is [MATH]f(x)=f(0)+xf'(0)+o(x)[/MATH]; substituting [MATH]x^2[/MATH] in the formula I get [MATH]f(x^2)=f(0)+x^2 f'(0)+o(x^2)[/MATH], so
[MATH]\lim_{x \to 0} \frac{f(x^2)-f(0)}{x}=\lim_{x \to 0} \frac{f(0)+x^2 f'(0)+o(x^2)-f(0)}{x}=\lim_{x \to 0} \frac{x^2 f'(0)+o(x^2)}{x}=\lim_{x \to 0} \left[xf'(0) +\frac{o(x^2)}{x}\right]=0+0=0[/MATH]Where I used the fact that [MATH]f'(0)=l\in\mathbb{R}[/MATH] since by hypothesis [MATH]f[/MATH] is differentiable in [MATH]x=0[/MATH], so [MATH]f'(0)[/MATH] must be finite and real. Is this correct? I'm not sure if the following part is correct: "[MATH]f(x)=f(0)+xf'(0)+o(x)[/MATH]; substituting [MATH]x^2[/MATH] in the formula I get [MATH]f(x^2)=f(0)+x^2 f'(0)+o(x^2)[/MATH]".
[MATH]\lim_{x \to 0} \frac{f(x^2)-f(0)}{x}=0[/MATH]My try: [MATH]f[/MATH] is differentiable in [MATH]x=0[/MATH], so from the Taylor formula with center in [MATH]x=0[/MATH] it is [MATH]f(x)=f(0)+xf'(0)+o(x)[/MATH]; substituting [MATH]x^2[/MATH] in the formula I get [MATH]f(x^2)=f(0)+x^2 f'(0)+o(x^2)[/MATH], so
[MATH]\lim_{x \to 0} \frac{f(x^2)-f(0)}{x}=\lim_{x \to 0} \frac{f(0)+x^2 f'(0)+o(x^2)-f(0)}{x}=\lim_{x \to 0} \frac{x^2 f'(0)+o(x^2)}{x}=\lim_{x \to 0} \left[xf'(0) +\frac{o(x^2)}{x}\right]=0+0=0[/MATH]Where I used the fact that [MATH]f'(0)=l\in\mathbb{R}[/MATH] since by hypothesis [MATH]f[/MATH] is differentiable in [MATH]x=0[/MATH], so [MATH]f'(0)[/MATH] must be finite and real. Is this correct? I'm not sure if the following part is correct: "[MATH]f(x)=f(0)+xf'(0)+o(x)[/MATH]; substituting [MATH]x^2[/MATH] in the formula I get [MATH]f(x^2)=f(0)+x^2 f'(0)+o(x^2)[/MATH]".